1995
DOI: 10.1073/pnas.92.17.8078
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antigen-specific cytolytic T cells in situ in human melanoma by immunization with synthetic peptide-pulsed autologous antigen presenting cells.

Abstract: Human melanoma cells can process the The discoveries of genes encoding a number of human melanoma-associated antigens (1-6) and of sequences of antigenic peptides serving as the cytolytic T-lymphocyte (CTL) epitopes on the appropriate major histocompatibility complex (MHC)class I molecules (7-11) have raised considerable interest in peptide-based specific melanoma vaccines. All the CTLdetermined melanoma-associated peptide epitopes that have so far been described are, however, "self' peptides (i.e., without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
140
1
4

Year Published

1997
1997
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(145 citation statements)
references
References 15 publications
0
140
1
4
Order By: Relevance
“…Some of these antigens are expressed in various tumours of different histological origins, but not in normal tissues other than testis. Therefore, these antigens have been designated cancer-testis antigens (CTAs) and their characteristics make them promising candidates for cancer-specific immunotherapy; clinical trials using peptides such as MAGE-1 or MAGE-3 are in progress for malignant melanoma (Mukherji et al, 1995;Marchand et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these antigens are expressed in various tumours of different histological origins, but not in normal tissues other than testis. Therefore, these antigens have been designated cancer-testis antigens (CTAs) and their characteristics make them promising candidates for cancer-specific immunotherapy; clinical trials using peptides such as MAGE-1 or MAGE-3 are in progress for malignant melanoma (Mukherji et al, 1995;Marchand et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Professional APC are characterized by their constitutive high levels of major histocompartibility complex (MHC) class II expression, poor phagocytic ability, lack of sIg and Fc receptors, weak adherence to solid supports [34] and their ability to stimulate primed T cell proliferation in an antigen specific manner [29]. Studies have clearly shown that peritoneal macrophages are highly proliferating progenitors for functional DC [24,28]. Several groups have succeeded in generating large numbers of functional DC from their proliferating progenitors located in bone marrow, spleen or blood in the presence of appropriate cytokines [2-4, 8, 10, 18, 19, 22].…”
mentioning
confidence: 99%
“…First preliminary data on the e ciency of antigen-presenting cells such as GM-CSF stimulated monocytes injected intradermally were obtained in melanoma patients. Induction of MAGE-1 MHC class I restricted peptide speci®c CTL were induced by vaccination which also recognized autologous melanoma cells, however in the absence of signi®cant clinical response (Hu et al, 1996;Mukherji et al, 1995). A pilot study using idiotype protein pulsed DC generated from circulating DC precursors (Markowicz and Engleman, 1990) was performed in four patients with malignant B cell lymphoma who had failed conventional chemotherapy.…”
Section: Clinical Trialsmentioning
confidence: 99%